Desenvolvimento de um dispositivo para medição de vibrações baseado em acelerômetros MEMS - Romanssini, Marcelo (2021)
Vibration meters are widely used in predictive maintenance on rotating electrical machines. One of the main techniques of predictive maintenance is vibration monitoring. The problems that manifest themselves in machines usually change their vibration patterns. There are equipment and systems capable of performing vibration measurements on the market. These devices use different types of transducers. The piezoelectric accelerometers are widely used due to their accuracy, but they have a high cost. Therefore, in this work we propose the design and development of a vibration meter based on MEMS accelerometers, since the manufacturing technology and accuracy of MEMS accelerometers has been the subject of much research and has evolved a lot in the last few years. The proposed system consists of two accelerometers, a three-axis digital accelerometer, in which it is possible to measure acceleration in x, y and z axis, and a uniaxial analog accelerometer. The analog accelerometer will be implemented on a dedicated circuit board and it can be connected and disconnected from the vibration meter as needed. The system is power supplied by a lithium ion battery. For data reading, system control, processing and sending data to a final device, the ESP32-WROOM-32 microcontroller was used. It has a processing unit, memory, Wi-Fi and Bluetooth module in the same device, which facilitated the implementation of the device. The acceleration data provided by the accelerometers after being digitized are read by the microcontroller through the SPI communication protocol and then sent to the final device through Wi-Fi, where the analysis is carried out, eliminating any type of physical connection between the devices, measurement and analysis. For the proposed system, circuits for load control, signal conditioning, voltage conditioning were designed and, finally, the prototype of the vibration meter was implemented. With the acquisition board in prototype, the software was written in the microcontroller and tests were carried out to validate the implemented circuits. The acceleration data captured through the embedded sensor was also tested. Finally, a vibration reading test was performed on an electric motor installed on a bench. With the tests carried out, we achieved good results, proving the operation of the designed circuits and the proposed system.